Does microgravity effect on oral and maxillofacial region?. Issue 5 (26th October 2020) - Stevens, Mark; Keyhan, Seied Omid; Ghasemi, Shohreh; Fallahi, Hamid Reza; Akbarnia, Shahriar; Dashti, Mahmood; Akbar Boojar, Fargol Mashhadi; Zadeh, Maneli Ardeshir; Cheshmi, Behzad
Abstract: Since the beginning of the era of space travel, there have been mentions of related health effects. Various studies have described the effect of space travel and microgravity on health. Some of these studies involved short and extended follow-ups of the effect of microgravity on the head and neck of astronauts. Therefore, we aimed to analyse the oral and maxillofacial health effects associated with this sophisticated mission. It is essential to identify relevant problems and address microgravity complications. Humans have long dreamed of flying and in recent years, the dream has evolved to exploring space and creating new habitats on other planets such as Mars. This led to an increase in the need for dental treatment of the flight crew members, which led to the creation of aviation dentistry for the screening and treatment of the oral cavity of the flight crew. We are moving towards a more conservative approach than before, such as removing pulpless teeth in aircrew patients or extracting roots that had a fracture or incomplete extraction. With all the advancements in aerospace knowledge, the aviation dentistry has rarely or briefly been discussed in dental textbooks. Dentists must screen each flight crew member thoroughly and impose flight restrictions and ground them if necessary; the reasons will be discussed later within this paper. It is the duty of dentists and surgeons to notify their patients (aircrew members) about the postoperative flight consequences and restrictions.